Research of Klebsiella pneumoniae in dairy herds - Langoni, Helio [UNESP]; Guiduce, Marcos Vinicius S. [UNESP]; Nobrega, Diego B. [UNESP]; Silva, Rodrigo C. da [UNESP]; Richini-Pereira, Virginia B. [UNESP]; Salina, Anelise [UNESP]; Guimaraes, Felipe de F. [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2015)
Klebsiella pneumoniae is a common environmental agent of clinical and subclinical mastitis affecting dairy herds, and may be present in the final product decreasing its quality. Mastitis caused by K. pneumoniae is even more severe due to its poor response to antibiotic therapy, rapid evolution to toxic shock and death of the animal. This paper aimed to study the prevalence of this pathogen among dairy herds in ten farms located in different municipalities of Sao Paulo State based on size and use of milking technology. All mammary glands of all lactating cows were screened using the California Mastitis Test (CMT) and a strip cup. A single aseptic milk sample (20mL) was collected from all CMT-positive quarters and bulk tanks, whereas swab samples were collected from feces, hind limbs of the animals, bedding and milking parlor. Identification of K. pneumoniae was performed using conventional microbiology culture, biochemical assay and Polimerase Chain Reaction. The primers were designed and tested at the Laboratory of Molecular Biology applied to Zoonoses (FMVZ, Unesp-Botucatu) targeting the 16S rRNA gene. This study included 1067 animals. Six cases of intramammary infection by K. pneumoniae were detected in six different cows in two farms. Moreover, K. pneumoniae was isolated in 77 swabs (34 from bedding in 9 farms, 7 from waiting rooms in 5 farms, 6 from milking parlors in 4 farms, 11 from rectums in six farms, and 19 from hindlimbs in 7 farms. Molecular analysis confirmed the agent was K. pneumoniae. At least one strain of the agent was identified in a certain site in all farms, showing the need of maintaining the hygiene in dairy farms.

Klebsiella pneumoniae é um agente ambiental comum de mastite clínica e subclínica que afetam vacas leiteiras e pode estar presente no produto final, reduzindo a sua qualidade. Mastite causada por K. pneumoniae é ainda mais grave devido à sua má resposta à antibioticoterapia, rápida evolução para choque tóxico e morte do animal. Este trabalho teve como objetivo estudar a prevalência deste patógeno entre os rebanhos leiteiros em dez fazendas localizadas em diferentes municípios do Estado de São Paulo com base no tamanho do rebanho e uso de tecnologia de ordenha. Todas as glândulas mamárias das vacas em lactação foram examinadas usando o California Mastitis Test (CMT) e caneca de fundo telado. Foram colhidas amostras de leite (20mL) de todos os quartos CMT- positivos e dos tanques de expansão, também foram colhidos swab de fezes, membros posteriores dos animais, cama dos animais e sala de ordenha. O isolamento e identificação de K. pneumoniae foi realizada através de cultura microbiológica convencional, ensaio bioquímico e Reação em Cadeia da Polimerase, utilizando primers desenhados e testados no Laboratório de Biologia Molecular aplicada à Zoonoses (FMVZ, Unesp-Botucatu) com base na região do gene de 16S rRNA. Este estudo incluiu 1067 animais. Foram detectados seis casos de infecção intramamária por K. pneumoniae em seis diferentes animais em duas fazendas. Ainda, K. pneumoniae foi isolada em 77 swabs (34 de camas em 9 propriedades, 7 de salas de pré-ordenha em 5 propriedades, 6 de salas de ordenha em 4 propriedades, 11 do reto de animais em 6 propriedades e 19 de membros posteriores em 7 propriedades. A análise molecular confirmou o agente K. pneumoniae. K. pneumoniae foi isolada pelo menos em uma localização em todas as propriedades leiteiras., salientando a necessidade de manter a higiene nas fazendas leiteiras a fim de controlar a mastite por esse patógeno.
Pesquisa de Klebsiella pneumoniae em rebanhos leiteiros
Keywords: Environment; Klebsiella pneumoniae; Milk; Mastitis; Dairy herds; Ambiental; Klebsiella pneumoniae; Leite; Mastite; Bovinos